Analysis of The Level of Slum Area in Subulussalam City - Teuku Jaswadi; Lita Sri Andayani; Rujiman (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
This study aims to analyze the level of slum area in Subulussalam City. The location of the study is conducted in Subulussalam City, Aceh Province, based on the Decree of the Mayor of Subulussalam No. 188.45 / 101/2014 concerning the determination of the location of slums in Subulussalam City, there are 5 slum areas with a total area of ​​61.77 hectares spread across 5 villages in 5 sub-districts which receive priority handling of slums through the KOTAKU program. The result shows that slum areas in Subulussalam City showed similarities with the results of Anggara's analysis (2018) of slum areas in Tanjung Beringin District, Serdang Bedagai Regency, which is at Medium slum level with a score of 64.